Politics of religiously motivated lending: an empirical analysis of aid allocation by the Islamic Development Bank - Hernández, Diego; Vadlamannati, Krishna Chaitanya (Journal of comparative economics, 2017)
We investigate whether lending by the Islamic Development Bank mirrors Saudi Arabia's political interests based on religious affinity using panel data for its 56 member countries over the 1970-2007 period. Our results indicate that Sunni regime countries receive favorable treatment in terms of loan allocation, as well as Shia majority populated countries in exceptional occasions of conflict with other religious minority groups, while non-Muslim countries are the least favored. There is also evidence that lending by the World Bank to the same group of countries and over the same time frame does not respond to the political stance of Saudi Arabia founded on religion. These findings reveal the advantage that Saudi Arabia gains by assuming the leadership of a Regional Development Bank in contrast to coordinating common strategies in a global International Financial Institution with other large shareholders for whom religion might not be essential for political alliances.